Korupsi Sebagai Sebuah Budaya - Syaripulloh (STIT Muslim Asia Afrika, 2021)
This paper wants to try to see the corruption of the concept of Islam and culture that does occur in the community, especially the people of Indonesia. Using the library approach, this paper is expected to have a new perspective in the form of learning for the people of Indonesia. The results were concluded that corruption is part of a culture.